Between Rejection and Revitalization: Tokunboh Adeyemo and African Traditional Religions - Veelen, Wouter van (2021)
Abstract This article analyzes Tokunboh Adeyemo’s assessment of African traditional religions in relation to his allegiance to the worldwide evangelical tradition. In the 1970 and 1980s, Adeyemo, who served as the General Secretary of the Association of Evangelicals in Africa, was involved in the so-called salvation debates within evangelical circles. Concerned about the rise of contextual theologies on the African continent, Adeyemo, like his predecessor Byang Kato, advocated the exclusive character of Christianity in terms of salvation. Therefore, he is sometimes described as someone who attempted to replace African religiosity with a Westernized form of Christianity. This article argues that while Adeyemo reiterates the uniqueness of salvation in Christ, as attested within the international evangelical movement, he offers a nuanced assessment of pre-Christian religiosity. Navigating between the two positions of rejection and revitalization, he pioneered new ways of developing an authentic evangelical theology that is grounded in the African context.
Keywords: salvation debate; inculturation theology; cosmological balance; African traditional religions (ATR); African evangelical theology; African Theology